Kepemimpinan Visioner dalam Manajemen Pendidikan: Studi Kualitatif di Sekolah Berbasis Nilai Karakter - Mashuri, Mashuri; Eliza, Mutia; Isnaini, Isnaini; Yusnimar, Yusnimar; Ramadona, Aulia (Universitas Batanghari Jambi, 2025)
This research aims to explore how school principals implement visionary leadership in building an educational environment that integrates character values into policies, programs and daily practices. This research uses a qualitative approach with a case study method. Data was collected through in-depth interviews with school principals, teachers and students, as well as through direct observation and analysis of school documents. The research results show that visionary leadership plays a significant role in forming a school culture that is oriented towards character formation. Visionary leadership is not only a strategic instrument in education management but also a catalyst for creating a generation with character and ready to face global challenges.